An Analysis Of Product Quality At PT Sinar Sagara Sejahtera Sumedang - Apriani, Sabrina; Gumilang, Risa Ratna; Damayanti, Wulan Ariani (SINTESA, 2025)
The footwear industry in Indonesia has developed very rapidly and is characterized by many companies that produce quality sandals. The research focus of this thesis is how the quality of products at PT Sinar Sagara Sejahtera Sumedang This study aims to determine the quality of products at PT Sinar Sagara Sejahtera Sumedang and to find out the obstacles and solutions to product quality at PT Sinar Sagara Sejahtera Sumedang. The method used in this research is descriptive qualitative, with a purposive sampling technique with informants totaling 10 people. Data collection techniques from this study through observation, interviews, documentation, and triangulation. In analyzing the data that has been obtained using the Miles and Huberman model through stages, data collection, data reduction, data presentation, and conclusion drawing/verification. The results of this study indicate that product quality at PT Sinar Sagara Sejahtera Sumedang is classified as good and in accordance with conditions in the field, but there are still indicators that need to be improved in order to meet consumer expectations more optimally regarding product quality at PT Sinar Sagara Sejahtera Sumedang.